KEBIJAKAN NATION BUILDING MALAYSIA: ANALISIS ATAS HAMBATAN PENERAPANNYA - , AFIQ ISKANDAR NAZIEF, Dra. Ilien Halina, M.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Like other post colonial states, Malaysia obtained its independence before it was ready as a nation. The Malaysian national identity was still yet to be defined by the various ethnic groups living in the country. Just before its independence, Malaysia defined its national identity based on that of the dominant ethnic group and then the Malaysian government implemented various nation building policies, ranging from the classic one such as national education policy with emphasis on the use of national language in schools to unusual one such as affirmative action policy to improve equity and balance among Malaysiaâs social and ethnic groups. During implementation, those nation building policies faced various obstacles, mostly in the form of rejections from the minority ethnic groups. Further analysis shows that these rejections are actually representation of the clash of the nation- of-intents perceived by the dominant and minority ethnic groups.